Modelling of organic Rankine cycle power systems in off-design conditions: An experimentally-validated comparative study. (15th March 2017) - Dickes, Rémi; Dumont, Olivier; Daccord, Rémi; Quoilin, Sylvain; Lemort, Vincent
Abstract: Because of environmental issues and the depletion of fossil fuels, the world energy sector is undergoing many changes toward increased sustainability. Among the many fields of research and development, power generation from low-grade heat sources is gaining interest and the organic Rankine cycle (ORC) is seen as one of the most promising technologies for such applications. In this paper, it is proposed to perform an experimentally-validated comparison of different modelling methods for the off-design simulation of ORC-based power systems. To this end, three types of modelling paradigms (namely a constant-efficiency method, a polynomial-based method and a semi-empirical method) are compared both in terms of their fitting and extrapolation capabilities. Post-processed measurements gathered on two experimental ORC facilities are used as reference for the models calibration and evaluation. The study is first applied at a component level (i.e. each component is analysed individually) and then extended to the characterization of the entire organic Rankine cycle power systems. Benefits and limitations of each modelling method are discussed. The results show that semi-empirical models are the most reliable for simulating the off-design working conditions of ORC systems, while constant-efficiency and polynomial-based models are both demonstrating lack of accuracy and/or robustness. Highlights: Three methods are compared to simulate the off-design operation of ORC engines. Post-processed experimental measurements are used as reference database. Fitting and extrapolation capabilities of these 3 modelling paradigms are studied. Both component-level and system-level analyses are performed. Semi-empirical models demonstrate to be the best modelling approach.